To the memory of Alexej Sitenko (Oleksij Sytenko) (Condensed Matter Physics, 2002)
Ukrainian and world science has suffered an irrelievable loss. A promine
nt the-
orist in physics, brilliant individual, true Ukrainian patriot Alexej Sitenk
o (Oleksij
Sytenko) passed away on February 11, 2002, one day before his 7
5th birthday.